Whole sugar 2, 3-butanediol fermentation for oil palm empty fruit bunches biorefinery by a newly isolated Klebsiella pneumoniae PM2. (August 2021) - Rehman, Shazia; Khairul Islam, Md; Khalid Khanzada, Noman; Kyoungjin An, Alicia; Chaiprapat, Sumate; Leu, Shao-Yuan
Graphical abstract: Highlights: A novel xylose-utilizing strain was newly isolated for 2, 3-BDO bioproduction. Sulfite-pretreated oil palm empty fruit bunches whole sugars were fermented. High 2, 3-BDO titer of 75 g/L was achieved via staged-fed batch SHF. A maximum of 0.48 g/g 2, 3-BDO on glucose and xylose was yielded. 135 kg 2, 3-BDO and 14.5 kg acetoin precursors were obtained from 1 tonne biomass. Abstract: Effective utilization of cellulose and hemicelluloses is essential to sustainable bioconversion of lignocellulose. A newly isolated xylose-utilizing strain, Klebsiella pneumoniae PM2, was introduced to convert the biomass "whole sugars" into high value 2, 3-butanediol (2, 3-BDO) in a biorefinery process. The fermentation conditions were optimized (30°C, pH 7, and 150 rpm agitation) using glucose for maximum 2, 3-BDO production in batch systems. A sulfite pretreated oil palm empty fruit bunches (EFB) whole slurry (substrate hydrolysate 119.5 g/L total glucose mixed with pretreatment spent liquor 80 g/L xylose) was fed to strain PM2 for fermentation. The optimized biorefinery process resulted in 75.03 ± 3.17 g/L of 2, 3-BDO with 0.78 ± 0.33 g/L/h productivity and 0.43 g/g yield (87% of theoretical value) via a modified staged separate hydrolysis and fermentation process. This result is equivalent to approximately 135 kg 2, 3-BDO and 14.5 kg acetoin precursors from 1 ton of EFB biomass without any wastage of both C6 and C5 sugars.